PENINGKATAN PRESTASI BELAJAR PESERTA DIDIK PADA KOMPETENSI DASAR MAKING BED DENGAN METODE TUTOR SEBAYA - VIVI AFIANTY (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to explain the Peer Tutor Method in an effort to improve learning achievement of basic competencies in making bed for class XI Hospitality Accommodation 3. This research approach uses classroom action research. The stages of the research include (1) identifying the problem, (2) making preparations, (3) preparing an action plan, (4) implementing actions, (5) making observations, and (6) compiling reports. The research process was carried out in two cycles, each cycle consisting of four stages, namely: (1) action planning, (2) action implementation, (3) observation and interpretation, and (4) analysis and reflection. Based on the research that has been done, it can be concluded that there is an increase in learning achievement in the practice of making bed with Peer Tutor learning methods. This is reflected in several assessment elements as follows: (1) Students who are declared to play an active role during learning activities which include: Student activity during apperception by 81.18% in cycle 1 increased to 87.21% in cycle II. The activeness of students in the group when participating in learning by 80% in the first cycle increased to 86.76% in the second cycle, (2) Students who were declared competent in making bed practice activities took place by 67% in the first cycle increased to 94.12% in the second cycle, (3) Based on the results of the final written test evaluation in the first cycle, it can be identified that students who have been able to work on the basic competency practice questions of making bed and get a score of 75 and above are 73.53% while in the second cycle it is 97%, by Therefore, one of the teacher's efforts to improve the practical ability of students on the basic competence of